(3TQM GdjGSejfjIs - (3TgGH GdOjf CHh GdYHGS CMeO Hf eMeO Hf Ydj GdTgjQ HGHf GdgGFes; (3YHO Gddg Hf eMeO Hf MLGL, CHh eMeO GdeYQha H` GHf GdjGSejf,J (B601 (3g` s ((3eMeO GdWfOJGdi GdCRgQi s)
(3ChdgG (B:s
(3Ef Yde GdLHQ hGdebGHdI ef CLd GdYdhe dG eMGdI , hXghQg YXje bOQg eZf Yf fUd OdGdg s
(3BNQgG (B:s
(3hEdi eG Hbi ddhQKI cGf GdeLJeY KdGKeGFI hGddg SHMGfg hJYGdi GYde s
(3GdfSNI HgG MhGTs
(3HBNQg eSCdIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdQjGVjGJs